Pengembangan Media Tangram Materi Bangun Datar untuk Meningkatkan Minat Belajar Siswa Kelas II MIS Ikhwanul Muslimin - Nesta Marienty Partisya; Nurdiana Siregar; Lailatun Nur Kamalia Siregar (Journal Innovation In Education, 2024)
The research that has been carried out is entitled “Development of tangram media with flat material to increase interest in learning for class II MIS Ikhwanul Muslimin” and is based on the learning phenomenon which still revolves around the teacher, the unavailability of learning media, and low interest in learning which makes the class atmosphere less fun and finally sleepy. Tangram media is an educational game that can increase interest in learning about flat shapes. This research aims to develop tangram media to increase interest in learning mathematics. The teaching material presented in this development is class II flat figures. The subjects in this research were students in class II-A MIS Ikhwanul Muslimin. Tangram media development procedures in this research refer to research and development with the ADDIE development code, which goes through the stages : analysis, design, development, implementation, and evaluation. Data collection methods use observation, interviews, questionnaire contents. Data collection techniques use validation, questionnaires and tests. All instruments used have gone through the validation stage by experts. The results of this research show that the validity of the material expert obtained a score of 75% in the valid category, then the validation expert obtained a score of 98% in the very valid category, the two scores were averaged to obtain the final validation score, so the final result of the validation was 86,5% in the very valid category. Based on the results of the practicality of tangram media obtained from the responses of 26 students 98% were in the very practical category, then the teachers response obtained a score of 96% in the very practical category, so that the average score obtained from the two practical respondents was 97% in the very practical category. Whilw the level of effectiveness using the N-Gain formula and obtaining an average N-Gain score reached a score of 0,88 which is a percentage of 88% in the high category. Thus, the development of tangram media is very effective in increasing interest in learning mathematics.